ChemInform Abstract: Heusler‐Alloy Films for Spintronic Devices. Issue 43 (7th October 2013) - Hirohata, Atsufumi; Sagar, James; Lari, Leonardo; Fleet, Luke R.; Lazarov, Vlado K.
Abstract Review: 27 refs.